The Mapping of Digital Culture Among Higher Education Lecturers in Indonesia (A Multisite Study) - Syamsuddin Syamsuddin; Nur Alim; Nina Ayunia Salbiyah (Ta'dib, 2025)
This study aims to analyze and construct a mind map of the digital culture of lecturers in higher education and its implications for the implementation of the Tri Dharma of Higher Education in the digital era. Using qualitative research with a multisite study design, data were collected through interviews, observations, and document analysis at IAIN Kendari and Universitas Muhammadiyah Kendari. The findings indicate that the digital culture of lecturers plays a crucial role in enhancing the effectiveness of teaching, research, community service, and faculty administration. Several key aspects were identified, including the development of digital competencies, innovation in teaching methods, and improved information accessibility among faculty and students. The study also revealed that despite progress in the adoption of digital technologies, challenges remain, such as insufficient training and resistance to changes in work culture due to digital transformation. Therefore, it is recommended that higher education institutions provide more intensive support for the development of digital culture and technological infrastructure. Thus, this research not only provides an overview of the digital culture of lecturers but also successfully constructs a mind map that simultaneously offers strategic recommendations for improving the quality of Tri Dharma implementation in the digital era.